(untitled) (Journal of Surgical Sciences, 2021)
The role of biliary decompression prior to definitive surgery in patient with distal malignant obstruction remains controversial.Many authors put their views in favor; because of improvement of liver functions and reticulo-endothelial function after decompression resulting in uneventful postoperative outcome and many others are against because of increase the risk of postoperative morbidity and mortality. We found the patients who underwent prior biliary decompression had unusual development of organisms in their bile which are found frequently resistant to usual antibiotics and most of them developed postoperative complications. Several other studies concluded in between that preoperative drainage should be performed in selected patients; delaying of surgery for any cause, presence of severe cholangitis, severe jaundice and poor nutrition and where hepatic resection is required along with pancreatoduodenectomy. We therefore concluded that biliary decompression should not routinely be performed except in special situations in patients with distal malignant biliary obstructionbefore pancreatoduodenectomy. Journal of Surgical Sciences (2020) Vol. 24 (2) : 66-69